QUALIFICATION OF PHYSICS TEST INSTRUMENTS LIKE-PISA - Rangkuti, Khairina; Bunawan, Wawan ((IPER) Indonesian Physics Education Research, 2022)
This research aims to develop a physics test instrument based on scientific literacy PISA (Program for International Student Assessment). Development of test instruments using 4D models (Define, Design, Development, Disseminate). The test instrument was tested by expert validity with a CVI score of 1. The test instrument tested involved 130 participants. The results of the item validity test showed that the 20 items tested were valid with a Cronbach Alpha reliability value of 0.816 ("very good" category). The discrimination power test results showed that the developed items are in the "good" and "very good" categories. The results of the difficulty level test showed that there was one difficult item, 11 medium questions, and eight easy questions. This research shows that the physics science literacy skills of students who participate in this research show that students achieve good scores on average. Students who participated in this research had the highest achievement in the competence of evaluation and design of scientific investigations and had the same achievement in both the content and the procedural knowledge aspects